The Representation of the Last Judgment in the Ikvi Murals - Gedevanishvili, Ekaterine (Actual Problems of Theory and History of Art, 2013)
The present paper is dedicated to the representation of the “Last Judgment” in the Church of Ikvi in Georgia. The author’s special concern is to explain the depictions of the “Entry into Jerusalem” and the “Communion of Sts. Paul and Peter”, unusual in the context of this iconographic programme.
Keywords: mediaeval Georgian art; Ikvi murals; Last Judgment; Entry into Jerusalem; Communion of Sts. Paul and Peter; Second Coming